CHALLENGES AND FACTORS INFLUENCING THE IMPLEMENTATION OF CLINICAL SKILL TRAINING AS A TRANSITION TO CLERKSHIP COURSE - Aisyah, Windy Nurul; Hidayah, Rachmadya Nur; Suhoyo, Yoyo (Universitas Gadjah Mada, 2023)
Background: Transitioning from a preclinical environment to clinical practice requires different skills than academic abilities. Medical students and tutors must make various adaptations that can be challenging during the clinical transition. Efforts to improve student preparation to face the transition from preclinical to clinical can be done with transition-to-clerkship courses (TTCC). The purpose of this study is to find out the benefits and challenges of implementing the Clinical Skill Training (CST) program as a transition-to-clerkship course (TTCC)Methods: Qualitative research with a case studies approach was performed using purposive sampling. Focus Group Discussion (FGD) and the in-depth interview continued until data saturation was reached, after that thematic analysis approach was used to do the analysis.Results: Students stated that CST is a learning program aimed at refreshing or recalling previously obtained material. Apart from being a material refresher program, CST facilitates peer learning about exchanging information and giving each other feedback. The tutors thought that CST can bridge the knowledge gap possessed by previous students regarding a disease diagnosis. The link between theory and practice of action will be strengthened during CST. The challenges include supervisor absence, lack of facilities, short intervention time, incomplete evaluation tools, and lack of clinical case variety.Conclusion: The implementation of CST can improve clinical reasoning, provide focused skills learning, and as a good transition program. This study should be used as feedback for the CST program, and further study is suggested to generalize the findings nationwide.